As Mudanças de Mandato Eletivo e as Suas Relações Com a (Re)Produção das Práticas dos Servidores Públicos Efetivos Municipais - Malavasi, Franciane Ribeiro (2024)
This study aims to understand relationships between the (re)production of practices in the performance of municipal civil servants and the transitions of municipal governments, from the perspective of retired former permanent municipal civil servants. Government transitions outline an interesting scenario in public organizations and allow us, within the theoretical perspective of practices, to discover how civil servants' practices manifest themselves. In this research, knowledge is a verb, knowing, and therefore it is not treated as something that belongs to the individual, as an object. The methodology adopted in this study was a descriptive qualitative research, carried out with 20 retired permanent civil servants who worked in 04 city halls located in the mountainous region of Espírito Santo, the information collection was carried out through documentary research, semi-structured interviews and the technique interview with the double. Using Creswell's spiral analysis technique, we identified that the (re)production of the practices of retired permanent public servants is manifested in knowing as a process of experience, as a neutral behavior within an environment of nonneutrals, as a process of adaptation and transformation, and as a security process. As a result, we observed that knowledge in practice became knowledge that constituted the practices of civil servants, because each experience in the face of the changes in mandate experienced by them enabled their (re)production. The results reveal that government transitions influence public service practices, because they are innovated through their expertise and knowledge. Civil servents, in the search for survival in these spaces, use practices, with an emphasis on the knowledge embedded in them, as a resource to reinforce their belonging to these organizations. Through the facets of knowing that we present in this study, the practices of permanent employees are (re)produced as a way of legitimizing their place as practitioners within the community of practice, in this case inb public organizations. This research contributed to understanding the (re)production of civil servants' practices in the face of factors involving government transitions.